The Pancasila Law State: Muhammadiyah's Contribution to Building the Indonesian Legal Paradigm - King Faisal Sulaiman; Husni Amriyanto (Universitas Muhammadiyah Yogyakarta, 2023)
Pancasila as Darul Ahdi Wa Syahadah in the perspective of Muhammadiyah opens a new interpretation space for the conception of the state law of Pancasila. This is quite logical because the 1945 Constitution only mentions Indonesia as a state of law without explaining its paradigmatic framework in a normative-systematic manner. The idea of Pancasila law (rechtsidee), which is full of ethical values, morals, customary law, and local wisdom, is still being degraded by the strong penetration and influence of the values of Western legal traditions, civil law, and common law. In contrast, the Western legal tradition is oriented towards the liberal-capitalist ideology, which contrasts with the Pancasila ideology. This research examined the problem of the current constitutional paradigm of national law development and investigated the strategy for strengthening Pancasila as the main paradigm for the development of national law and the concept of the ideal state of Pancasila law from the perspective of Darul Ahdi Wa Syahadah. This normative-empirical research had three main components: The first was a literature study to identify and map polemics over a number of related legal products. The second part was a field study by observation and direct interviews (purposive sampling/non-random sampling) with a number of associated informants. Lastly, the third part was the analysis of results, conclusions, and recommendations. As a result, this research produced policy formulations related to strengthening Pancasila as a paradigm of national law development and the ideal concept of a state of law Pancasila from the future perspective of Darul Ahdi Wa Syahadah.